An assessment of the G20's initial action items - Nicolas Véron (Bruegel, 2010)
In this policy contribution, Bruegel Senior Fellow Nicolas Veron and Stephane Rottier, National Bank of Belgium, score and grade the implementation and follow up of the 47 action items that were outlined in the G20 summit in 2008. This paper complements their policy brief titled 'Not all financial regulation is global'.
Keywords: 330; Finanzmarkt; Regulierung; Bewertung; G-20-Staaten